ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 316 K/TUN/2021 TENTANG PENYELESAIAN SENGKETA SERTIFIKAT GANDA BERDASARKAN ASAS UMUM PEMERINTAHAN YANG BAIK (AUPB) - Azizah, Fitrotul; Susilowati, Indri Fogar (NOVUM : JURNAL HUKUM, 2022)
This research analyzes Supreme Court Decision No. 316 K/TUN/2021, where the judges only considered the aspects of authority and land registration procedures up to the issuance of property rights certificates. The focus of this study is the ambiguity in the judges' considerations, as seen in Article 10, which is the basis for the plaintiff's lawsuit regarding the carelessness of the Land Office in issuing property rights certificates, thus causing legal uncertainty. This research uses a normative legal approach with methods including legal, conceptual, and case studies. The analysis results show a violation of the General Principles of Good Governance (AUPB), particularly the principles of legal certainty and accuracy. The violation of legal certainty is related to the uncertainty of property rights over state land based on Article 55 (1) of Law No. 30 of 2014 on Public Administration. Meanwhile, the violation of accuracy occurs because the Lombok Barat Regency Land Office did not conduct document verification meticulously according to Articles 50 (1) and (2) of the same law. This research emphasizes the importance of the government ensuring that every stage of land registration is conducted accurately, especially in collecting physical data, legal data, and researching land ownership history according to applicable regulations. Keywords: Supreme Court Decision, property rights certificate, legal certainty principle, accuracy principle, AUPB.